I recently saw the derivation of length contraction in Special Relativity . At the end , it said(adsbygoogle = window.adsbygoogle || []).push({});

x' = (x - vt) γ(gamma)

x = (x' + vt') γ(gamma)

Where γ(gamma) is Lorentz transformation . It is = 1/√(1- v²/c²)

Then derivation continued , with expantion of x' = (x + vt)γ

As t = 0 in this case

We end up with , x'(√(1- v²/c²) ) = x

As √(1- v²/c²) is always between 1 and 0 , x ≤ x'

Thus , length of an object is contracted of any other observer ( if the speed of object is near the speed of light)

Now the question is , If we take x = (x' + vt') γ instead of x' = (x + vt)γ

We end up with x = (x')γ

and we take x' = (x + vt)γ (as we did above)

We end up with x' = (x)γ

How is this possible that

x = (x')γ and x' = (x)γ

If i have watched the wrong derevation , please send me the link of correct derevation .

**Physics Forums - The Fusion of Science and Community**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# B Length Contraction equation derivation

Have something to add?

Draft saved
Draft deleted

Loading...

Similar Threads - Length Contraction equation | Date |
---|---|

I What is the "limit of vanishing transport velocity"? | Mar 5, 2018 |

B How can I derive the law of composition of velocities? | Feb 10, 2018 |

I Interactive Minkowski Diagram Tool | Mar 26, 2017 |

I Subbing Planck length into length contraction equation? | Aug 11, 2016 |

Equations for length contraction | Apr 26, 2011 |

**Physics Forums - The Fusion of Science and Community**